Prevention and control of healthcare associated Infections within developing countries - Borg, Michael A (International Journal of Infection Control, 2009)
Many developing countries often face significant health and hygiene challenges that predispose to the transmission of infectious diseases within both community and healthcare settings. Deficient infrastructures, rudimentary equipment and a poor quality of care contribute towards incidences of nosocomial infections which have been estimated to be between 2-6 times higher than those in developed nations. This is the result of varying infrastructural and service deficits within healthcare facilities including inadequate or unsafe water supply, significant overcrowding due to inadequate beds to cope with demand as well lack of strategic direction and planning for healthcare delivery. In order to improve the effectiveness of infection control in many developing countries, a multifactorial set of initiatives needs to be undertaken that are both feasible as well as achievable in the background of economical and social deficits. Hand hygiene is probably the most cost effective of such interventions. One of the most effective methods for improving infection prevention and control within a country or region is to form an organization in which interested members interact regularly to review practices, share information and support each other. The International Federation of Infection Control (IFIC) provides a forum to link such societies and healthcare professionals working in infection control and related fields worldwide. In this way it is possible to draw on the expertise of its member organizations to network and communicate with each other and assist the development of infrastructure and output within countries that are in early stages of infection control development.